2017
DOI: 10.1088/1752-7163/aa66d3
|View full text |Cite
|
Sign up to set email alerts
|

Breath acetone as a potential marker in clinical practice

Abstract: In recent decades, two facts have changed the opinion of researchers about the function of acetone in humans. Firstly, it has turned out that acetone cannot be regarded as simply a waste product of metabolism, because there are several pathways in which acetone is produced or broken down. Secondly, methods have emerged making possible its detection in exhaled breath, thereby offering an attractive alternative to investigation of blood and urine samples. From a clinical point of view the measurement of breath a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 205 publications
1
77
0
3
Order By: Relevance
“…in vivo 33: 1165-1174 (2019) Acetone originates from breakdown of acetoacetate and αhydroxybutyrate, accompanying fatty acid degradation, glycolysis, and pyruvate metabolism (55-57). Acetone mouth odor is mainly associated with diabetes and halitosis, however, its higher level in body fluids may be used in clinical diagnostics (56)(57)(58). The metabolism of acetone is closely associated with the production of lactic acid, which in this study was increased, therefore can be the product, at least in part of acetone biotransformation (57).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…in vivo 33: 1165-1174 (2019) Acetone originates from breakdown of acetoacetate and αhydroxybutyrate, accompanying fatty acid degradation, glycolysis, and pyruvate metabolism (55-57). Acetone mouth odor is mainly associated with diabetes and halitosis, however, its higher level in body fluids may be used in clinical diagnostics (56)(57)(58). The metabolism of acetone is closely associated with the production of lactic acid, which in this study was increased, therefore can be the product, at least in part of acetone biotransformation (57).…”
Section: Discussionmentioning
confidence: 59%
“…Increased level of isopropanol in samples from CPD-affected patients is rather surprising, considering that it is used as a common disinfectant and antiseptic agent. However, the positive correlation between isopropanol and acetone was found, where acetone can also be the product of isopropanol breakdown (56).…”
Section: Discussionmentioning
confidence: 92%
“…Using a broadband tunable Tm/Ho-doped fiber laser (4780-5560 cm −1 ) and placing the sample inside the cavity, simultaneous detection of H 2 [119]. Furthermore, also broadband absorbing molecules, such as acetone [152], can be detected in breath samples with a portable and compact system. For example, Hancock et al have demonstrated lab-based mid-and near-IR CEAS systems for breath acetone detection [98,101].…”
Section: Opportunitiesmentioning
confidence: 99%
“…It can be conversed from acetoacetate and isopropanol in the human body. 30 The breath acetone is related to the blood glucose level, and may be used as an indicator for diabetes mellitus. 31,32 Indole and 2-furanmethanol have also been observed in the human breath in previous studies, 33,34 although their pathways are unclear.…”
Section: Source Analysis Of Nitrogen-containing Compoundsmentioning
confidence: 99%